Film-forming agent with conductivity and corrosion resistance as well as preparation method and application of film-forming agent
By adding materials such as zirconium salt, acid copolymer and oxidizer to water at low temperature, conductive corrosion-resistant nanomaterials, combined with acrylic homopolymer and neutralizing agent, the problem of poor performance of chromium-free passivation materials in the prior art is solved. It achieves both conductivity and corrosion resistance, meets the requirements of the mid-to-high-end market and improves environmental protection.
Patent Information
- Application Number
- CN202411541955.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, hexavalent chromium passivation technology is prohibited due to pollution problems, and it is difficult to develop chromium-free passivation materials that can meet the requirements of mid- and high-end markets. The existing alternative materials have poor performance. It is difficult to meet the high requirements of electronic devices.
Conductive corrosion-resistant nanomaterials are prepared by adding zirconium salts, acidic copolymers, oxidants and monomers to water at -2-2°C for reaction, and soluble zirconium salts and acidic copolymers provide a stable acidic environment and catalytic effect. A nanomaterial with conductive properties is formed and combined with an acrylic homopolymer and a neutralizing agent to prepare a film forming agent with conductive and corrosion resistance.
It achieves both conductivity and corrosion resistance, and can form a uniform and dense film layer on the metal surface, improve the conductive characteristics and corrosion resistance of the film layer, meet the requirements of the mid- and high-end markets, and has better environmental protection.
Smart Images

Figure CN119242115A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of film-forming agents, and in particular to a film-forming agent with electrical conductivity and corrosion resistance, and a preparation method and application thereof. Background Art
[0002] In the coating industry, coating pretreatment plays two main roles. On the one hand, it improves the adhesion of later industrial paints, and on the other hand, it improves the passivation effect of metal substrates. In many fields such as computer circuit boards, mobile phone circuit boards, and some die-cast aluminum parts in the automotive industry, paint is not required during the assembly process. The corrosion resistance of the entire component needs to be provided by the pretreatment film layer. Therefore, the pretreatment film layer is required to have good corrosion resistance. At the same time, since such electronic devices require better conductivity, the pretreatment film layer also needs to have good conductivity. At present, in this application scenario, the more mature ones are still trivalent chromium passivation and hexavalent chromium passivation technology, especially hexavalent chromium passivation technology, which can not only provide better corrosion resistance, but also give the passivation film layer better conductivity. However, due to the huge pollution problems of hexavalent chromium and trivalent chromium, such passivation technology has been gradually banned and eliminated by the market, especially for exported electronic devices. Therefore, the development of chromium-free passivation materials with conductivity and high corrosion resistance is urgent for the development of the industry. Existing technologies mainly focus on the exploration of systems or derivative systems such as phosphating, silane, zirconization, and rare earth salts. However, their performance is still far behind that of trivalent chromium or hexavalent chromium passivation technologies, and can only barely meet the requirements of the low-end market. There is a huge gap with the mid-end and high-end market requirements. Summary of the invention
[0003] In order to solve the above technical problems, the purpose of the present invention is to provide a film-forming agent with conductivity and corrosion resistance, and a preparation method and application thereof.
[0004] The above object of the present invention is achieved through the following technical solutions:
[0005] The first aspect of the present invention provides a conductive corrosion-resistant nano material, which is prepared by the following method: adding zirconium salt, acid copolymer, oxidant and monomer to water in sequence at -2 to 2°C to react, and obtaining the conductive corrosion-resistant nano material after the reaction is completed;
[0006] The acid copolymer is selected from one or more of acrylic acid-acrylate-sulfonic acid-phosphonate copolymer, acrylic acid-acrylate-hydrolyzed maleic acid copolymer and acrylic acid-acrylate-tartaric acid copolymer, and the monomer is selected from one or more of benzotriazole, phenol, thiophene and aspartic acid.
[0007] The reaction temperature for preparing the conductive corrosion-resistant nanomaterials of the present invention is controlled at -2 to 2°C, aiming to control the subsequent material synthesis rate by regulating the kinetic characteristics, thereby avoiding excessive local reaction that affects the activity and batch stability.
[0008] Furthermore, the zirconium salt is selected from one or more of zirconium nitrate, zirconium oxychloride, zirconium carbonate and zirconium fluoride.
[0009] The zirconium salt provided by the present invention is a soluble zirconium salt. The tetravalent zirconium salt has a strong hydrolysis ability and can be hydrolyzed into a hydrated zirconium ion equilibrium state under stirring conditions of 5 to 10 hours. On the one hand, it can promote the ionization of water into hydrogen ions, provide a relatively stable acidic environment for subsequent synthesis, and maintain the hydrogen ions within a certain equilibrium range; on the other hand, the hydrated zirconium ions can coordinate with the characteristic functional groups of subsequent monomers, participate in the synthesis of subsequent nanomaterials, and give the final nanomaterials film-forming properties.
[0010] The acidic copolymer provided by the present invention can, on the one hand, make up for the lack of the ability of soluble zirconium salt to provide acidic conditions during the hydrolysis process, because the acidic hydrogen ions play a catalytic role in the monomer polymerization synthesis process; on the other hand, it can participate in the subsequent synthesis of nanomaterials, and the phenolic hydroxyl groups in the acidified copolymer can coordinate with the monomers and hydrated zirconium ions, participate in the synthesis of nanomaterials, enhance the subsequent film-forming activity of the nanomaterials, and participate in the physical and chemical adsorption of the conductive film layer on the metal substrate.
[0011] Furthermore, the molecular weight of the acidic copolymer is 1000-5000Da, preferably 3000-5000Da.
[0012] Furthermore, the oxidant is a conventional oxidant for synthesizing polyelectrolytes, and can be selected from one or more of ammonium persulfate, sodium persulfate, hydrogen peroxide and potassium permanganate.
[0013] The oxidant provided by the present invention undergoes a redox reaction with the subsequent monomers, plays an oxidizing role, and promotes the polymerization synthesis of nanomaterials.
[0014] Exothermic reactions will occur during the polymerization synthesis of monomers, acidic copolymers, and hydrated zirconium ions. Therefore, ice cubes can be added after the oxidant is added to ensure that the solution temperature is maintained at -2 to 2°C to avoid local exothermic reactions that affect the synthesis of nanomaterials.
[0015] In the presence of acidic copolymers and oxidants, monomers begin to polymerize with protonated ammonia nitrogen elements and phenolic hydroxyl groups to form oxidized polymer nanomaterials. The protonated nitrogen atoms are also the key to ensuring that the nanomaterials have conductive properties after film formation. At this time, the material with passivation properties can passivate the metal interface to make the metal element form its oxidized form, thereby increasing the film potential and thus improving the corrosion resistance.
[0016] During the monomer polymerization process, acidic copolymers will participate in it. For example, carboxylic acid hydroxyl groups, sulfonic acid hydroxyl groups, and phosphonic acid hydroxyl groups will all seize the position of phenolic hydroxyl groups and can polymerize with protonated ammonia nitrogen to form larger irregular, indefinite sequence macromolecules. In addition, the chelating properties of carboxylic acid hydroxyl groups, sulfonic acid groups, phenolic hydroxyl groups, or phosphonic acid hydroxyl groups can chelate with metal ions to form amorphous polymeric nanomaterials. The surface of the material is rich in a large number of phenolic hydroxyl groups, and its hydroxyl groups can more easily cooperate in chemical or physical adsorption on the oxidized metal surface, thereby achieving the purpose of film formation on the substrate surface.
[0017] Furthermore, the mass ratio of the water, zirconium salt, acidic copolymer, oxidant and monomer is (85-96):(1-5):(1-5):(0.1-0.5):(1-5).
[0018] Furthermore, after the reaction is completed, the steps of washing, centrifugation and drying are also included.
[0019] The second aspect of the present invention provides a film-forming agent with conductivity and corrosion resistance, which is composed of the following components in percentage by mass: 1% to 5% of the conductive and corrosion-resistant nanomaterial described in the first aspect, 1% to 10% of acrylic acid homopolymer, 1% to 5% of a neutralizer, and the remainder being water.
[0020] Preferably, the film-forming agent is composed of the following components in percentage by mass: 2% to 5% of the conductive and corrosion-resistant nanomaterial described in the first aspect, 1% to 10% of acrylic acid homopolymer, 1% to 5% of neutralizer, and the remainder is water.
[0021] Furthermore, the molecular weight of the acrylic acid homopolymer is 3000-5000Da.
[0022] The acrylic acid homopolymer provided by the present invention has a better symmetrical structure and more abundant (carboxyl) hydroxyl groups. The hydroxyl functional group has stronger physical and chemical adsorption characteristics. The conductive corrosion-resistant nanomaterial has weak passivation performance. When it interacts with the metal surface, the metal element can form a metal oxide molecular layer. The hydroxyl group is more likely to be physically or chemically adsorbed on the metal oxidation state, thereby improving the adsorption strength, thereby playing a synergistic passivation role, making the film layer more uniform, and improving the film layer thickness and density.
[0023] Furthermore, the neutralizing agent is used to adjust the pH and can be selected from one or more of ammonia water, ammonium carbonate, ammonium bicarbonate, monoethanolamine and polyaspartic acid.
[0024] The third aspect of the present invention provides a method for preparing a film-forming agent with conductivity and corrosion resistance, comprising the following steps: dissolving the conductive and corrosion-resistant nanomaterial, acrylic acid homopolymer and neutralizer described in the first aspect in water to obtain the film-forming agent with conductivity and corrosion resistance.
[0025] The fourth aspect of the present invention provides an application of the conductive and corrosion-resistant film-forming agent described in the second aspect in metal surface coating, which can be widely used in various metal substrates such as iron, copper, aluminum, magnesium-aluminum alloy, etc., providing long-term corrosion resistance and excellent conductive properties.
[0026] Beneficial effects of the present invention:
[0027] The present invention adopts acid copolymer doping to prepare conductive corrosion-resistant nanomaterials, which not only provides acidic protonation conditions for monomer synthesis, but also utilizes the active hydroxyl groups (carboxylic acid hydroxyl, sulfonic acid hydroxyl, phosphine hydroxyl, etc.) in the acid copolymer to bond with protonated nitrogen atoms, robbing the characteristics of phenolic hydroxyl groups, so that it can effectively participate in the synthesis process of conductive corrosion-resistant nanomaterials, so that the polymer macromolecule (i.e. conductive corrosion-resistant nanomaterial) not only has the conductivity of conductive polymers, but also has the chelating adsorption film-forming characteristics unique to the acid copolymer band on the metal surface, and cleverly integrates the advantages of the two, so that the new structure has good conductive properties after being converted into a film on the metal surface. The introduction of zirconium ions utilizes the chelation of hydroxyl groups in the conductive corrosion-resistant nanomaterials with tetravalent zirconium ions to form an irregular nanostructure. As the final material chemically adsorbs and forms a film on the metal surface, the chelated zirconium ions participate in it to form "OH-ZrO 2 "Chemical state, improve the film rubbishability, eliminate film stress, improve the film density, thereby improving the final corrosion resistance of the film. In addition, as a corrosion-resistant additive, the conductive corrosion-resistant nanomaterial has the characteristics of passivating metals, making it easy for metal elements to oxidize to form oxide films. The inventors have found through a large number of studies that the hydroxyl group of acrylic acid homopolymer is more easily adsorbed on the surface of the metal oxide film, accelerating the film formation rate. Therefore, passivation and hydroxyl adsorption form a synergistic effect, which jointly promotes the protective effect of the metal surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XPS graph of the conductive and corrosion-resistant nanomaterial in Example 1.
[0029] Figure 2 This is the high-resolution XPS spectrum of the N element of the conductive and corrosion-resistant nanomaterial in Example 1.
[0030] Figure 3 This is the XPS graph of the conductive and corrosion-resistant nanomaterial in Example 2.
[0031] Figure 4 This is the high-resolution XPS spectrum of the N element of the conductive and corrosion-resistant nanomaterial in Example 2.
[0032] Figure 5 This is a SEM image of the passivation film surface of Example 1.
[0033] Figure 6 This is the SEM image of the passivation film surface of Example 2. DETAILED DESCRIPTION
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0035] The invention provides a conductive corrosion-resistant nano material, which is prepared by the following method: adding zirconium salt, acid copolymer, oxidant and monomer to water in sequence at -2 to 2°C for reaction, and obtaining the conductive corrosion-resistant nano material after the reaction is completed.
[0036] In a specific embodiment, the method for preparing the conductive corrosion-resistant nanomaterial comprises the following steps:
[0037] (1) Add water to the reactor and start stirring at a rate of 30 to 50 r / min;
[0038] (2) Turn on the circulating cooling device and cool the water to -2 to 2°C;
[0039] (3) Add zirconium salt and stir for 5 to 10 hours to promote hydrolysis equilibrium;
[0040] (4) Slowly add the acid copolymer while stirring, and stir for 3 to 5 hours to ensure uniform dissolution;
[0041] (5) Add oxidant and stir for 2 to 3 hours to make it dissolve evenly;
[0042] (6) Add ice cubes and increase the stirring rate to 50-60 r / min;
[0043] (7) Slowly add the monomer and continue stirring for 20 to 24 hours after the addition is completed;
[0044] (8) Using water as the permeation medium, the solution is filtered and cleaned by a semipermeable membrane permeation cleaning method to clean out the impurity ions in the solution. The single permeation time is 20 to 24 hours, and the permeation cleaning is performed 5 to 6 times;
[0045] (9) The solution after the permeate cleaning and filtration is centrifuged in an ultra-high speed centrifuge at a speed of 15,000 to 16,000 r / min for 30 to 40 min;
[0046] (10) vacuum drying the nanomaterials obtained by centrifugation at a drying temperature of 50 to 60° C., a heating rate of 0.1 to 0.5° C. / min, and a drying duration of 20 to 24 h;
[0047] (11) The dryer is cooled to room temperature at a cooling rate of 0.5 to 1° C. / min to obtain a conductive and corrosion-resistant nanomaterial.
[0048] The invention provides a method for preparing a film-forming agent with conductivity and corrosion resistance, comprising the following steps: dissolving a conductive and corrosion-resistant nano material, an acrylic acid homopolymer and a neutralizer in water to obtain the film-forming agent with conductivity and corrosion resistance.
[0049] In a specific embodiment, the method for preparing a film-forming agent having electrical conductivity and corrosion resistance comprises the following steps:
[0050] (1) Add water to the stirred tank and start stirring at a speed of 30 to 50 r / min;
[0051] (2) Add acrylic acid homopolymer and stir for 1 to 2 hours to achieve uniform dissolution;
[0052] (3) Add the conductive and corrosion-resistant nanomaterials and stir for 2 to 3 hours to fully disperse and dissolve them;
[0053] (4) Add a neutralizing agent, continue stirring for 1 to 2 hours, and add the remaining water to obtain a film-forming agent with conductivity and corrosion resistance.
[0054] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0055] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0056] However, in fact, the acidic copolymers produced by different manufacturers have differences in polymerization degree, polymerization sequence, polymerization molecular weight and other processes, which will seriously affect their performance. In the subsequent material synthesis, it will have a great impact on the size, water solubility and proton state of the nanomaterial, and may even lead to the consequence that the material cannot be synthesized. Therefore, the acidic copolymers (molecular weight of 3000-5000Da) in the following examples and comparative examples were purchased from Shandong Xintai Water Treatment Co., Ltd.
[0057] Acrylic acid homopolymer (molecular weight 3000-5000Da) was purchased from Shandong Taihe Water Treatment Company, model TH-455.
[0058] Example 1
[0059] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 2% conductive and corrosion-resistant nanomaterial, 1% acrylic acid homopolymer, 2% ammonia water, and the rest water;
[0060] The preparation method comprises the following steps:
[0061] (1) Add 50% pure water into the stirred tank and start stirring at a speed of 30 r / min;
[0062] (2) Adding acrylic acid homopolymer and stirring for 2 hours to achieve uniform dissolution;
[0063] (3) Add the conductive and corrosion-resistant nanomaterials and stir for 3 hours to fully disperse and dissolve them;
[0064] (4) Add ammonia water, continue stirring for 1 hour, and add the remaining amount of pure water to obtain a film-forming agent with conductivity and corrosion resistance.
[0065] Among them, the conductive and corrosion-resistant nanomaterial is prepared by the following method:
[0066] (1) Add 88.8% water into the reactor and start stirring at a stirring rate of 30 r / min;
[0067] (2) Turn on the circulating cooling device and cool the water to 0°C;
[0068] (3) Add 2% zirconium nitrate and stir for 5 hours to promote hydrolysis equilibrium;
[0069] (4) slowly adding 3% acrylic acid-acrylate-sulfonic acid-phosphonate copolymer while stirring, and stirring for 3 hours to ensure uniform dissolution;
[0070] (5) Add 0.2% ammonium persulfate and stir for 2 h to make it dissolve evenly;
[0071] (6) Add 1% ice and increase the stirring rate to 50 r / min;
[0072] (7) Slowly add 5% phenol and continue stirring for 24 h after the addition is complete;
[0073] (8) Using water as the permeation medium, the solution is permeated and cleaned by a semipermeable membrane permeation cleaning method to clean out the impurity ions in the solution. The single permeation time is 24 hours, and the permeation cleaning is performed 6 times;
[0074] (9) The solution after the permeate cleaning and filtration is centrifuged in an ultra-high speed centrifuge at a speed of 15000 r / min for 30 min;
[0075] (10) vacuum drying the nanomaterials obtained by centrifugation at a drying temperature of 60°C, a heating rate of 0.1°C / min, and a drying duration of 24 h;
[0076] (11) The dryer is cooled to room temperature at a cooling rate of 0.5°C / min to obtain a conductive and corrosion-resistant nanomaterial.
[0077] Figure 1 is the X-ray photoelectron spectroscopy (XPS) diagram of the conductive and corrosion-resistant nanomaterial in Example 1. Figure 1 The corresponding characteristic elements such as phosphorus, nitrogen, oxygen, carbon, etc. can be seen.
[0078] Figure 2 This is the high-resolution XPS spectrum of the N element of the conductive and corrosion-resistant nanomaterial in Example 1. Figure 2 It can be seen that there is a protonation characteristic peak in the N element, which is also the key to the conductivity of nanomaterials and passivation films.
[0079] Example 2
[0080] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 5% conductive and corrosion-resistant nanomaterial, 1% acrylic acid homopolymer, 2% ammonia water, and the rest water;
[0081] The preparation method is substantially the same as that of Example 1, except that the acrylic acid-acrylate-sulfonic acid-phosphonate copolymer is replaced by an acrylic acid-acrylate-hydrolyzed maleic acid copolymer.
[0082] Figure 3 This is the XPS graph of the conductive and corrosion-resistant nanomaterial in Example 2. Figure 4 This is the high-resolution XPS spectrum of the N element of the conductive and corrosion-resistant nanomaterial in Example 2.
[0083] Example 3
[0084] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 2% conductive and corrosion-resistant nanomaterial, 1% acrylic acid homopolymer, 2% ammonia water, and the rest water;
[0085] The preparation method is substantially the same as that of Example 1, except that the acrylic acid-acrylate-sulfonic acid-phosphonate copolymer is replaced by an acrylic acid-acrylate-tartaric acid copolymer.
[0086] Example 4
[0087] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 2% conductive and corrosion-resistant nanomaterial, 1% acrylic acid homopolymer, 2% ammonia water, and the rest water;
[0088] The preparation method is substantially the same as that of Example 1, except that phenol is replaced by thiophene.
[0089] Example 5
[0090] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 2% conductive and corrosion-resistant nanomaterial, 1% acrylic acid homopolymer, 2% ammonia water, and the rest water;
[0091] The preparation method is substantially the same as that of Example 1, except that phenol is replaced by aspartic acid.
[0092] Example 6
[0093] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 2% conductive and corrosion-resistant nanomaterial, 1% acrylic acid homopolymer, 2% ammonia water, and the rest water;
[0094] The preparation method is basically the same as that in Example 1, except that phenol is replaced by benzotriazole.
[0095] Example 7
[0096] A film-forming agent with conductivity and corrosion resistance is composed of the following components in percentage by mass: 1% conductive and corrosion-resistant nanomaterial, 1% acrylic acid homopolymer, 1% ammonia water, and the rest is water; the preparation method is basically the same as that of Example 1.
[0097] Example 8
[0098] A film-forming agent with conductivity and corrosion resistance is composed of the following components in percentage by mass: 5% conductive and corrosion-resistant nanomaterial, 10% acrylic acid homopolymer, 5% ammonia water, and the rest is water; the preparation method is basically the same as that of Example 1.
[0099] Example 9
[0100] A film-forming agent with conductivity and corrosion resistance is composed of the following components in percentage by mass: 1% conductive and corrosion-resistant nanomaterial, 10% acrylic acid homopolymer, 5% ammonia water, and the rest is water; the preparation method is basically the same as that of Example 1.
[0101] Example 10
[0102] A film-forming agent with conductivity and corrosion resistance is composed of the following components in percentage by mass: 5% conductive and corrosion-resistant nanomaterial, 1% acrylic acid homopolymer, 1% ammonia water, and the rest is water; the preparation method is basically the same as that of Example 1.
[0103] Embodiment 11
[0104] A film-forming agent with conductivity and corrosion resistance is composed of the following components in percentage by mass: 2% conductive and corrosion-resistant nanomaterial, 3% acrylic acid homopolymer, 3% ammonia water, and the rest is water; the preparation method is basically the same as that of Example 1.
[0105] Example 12
[0106] A film-forming agent with conductivity and corrosion resistance is composed of the following components in percentage by mass: 3% conductive and corrosion-resistant nanomaterial, 2% acrylic acid homopolymer, 2% ammonia water, and the rest is water; the preparation method is basically the same as that of Example 1.
[0107] Comparative Example 1
[0108] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 2% nanomaterial, 1% acrylic acid homopolymer, 2% ammonia water, and the rest water;
[0109] The preparation method is basically the same as that in Example 1, except that: compared with the preparation method of the conductive and corrosion-resistant nanomaterial in the example, the acrylic acid-acrylate-sulfonic acid-phosphonate copolymer is replaced by polyhydrolyzed maleic anhydride.
[0110] Comparative Example 2
[0111] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 2% nanomaterial, 1% acrylic acid homopolymer, 2% ammonia water, and the rest water;
[0112] The preparation method is basically the same as that in Example 1, the difference is that compared with the preparation method of the conductive and corrosion-resistant nanomaterial in the example, phenol is replaced by pyrrole.
[0113] Comparative Example 3
[0114] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 0.5% conductive and corrosion-resistant nanomaterial, 20% acrylic acid homopolymer, 10% ammonia water, and the rest water;
[0115] The preparation method is basically the same as that in Example 1.
[0116] Comparative Example 4
[0117] A film-forming agent with conductivity and corrosion resistance, composed of the following components in percentage by mass: 15% of conductive and corrosion-resistant nanomaterial, 1% of acrylic acid homopolymer, 2% of ammonia water, and the rest of water;
[0118] The preparation method is basically the same as that in Example 1.
[0119] Test Example 1
[0120] A 6061 aluminum profile was used as the experimental substrate. After cleaning, the experimental substrate was immersed in the film-forming agent prepared in Examples 1-12 and Comparative Examples 1-4 for passivation treatment for 15 minutes. After the treatment, it was cleaned and dried (dried at 60°C) to obtain a passivation film on the surface of the experimental substrate. The scanning electron microscope (SEM) image of the passivation film surface of Example 1 is as follows: Figure 5 As shown, the SEM image of the passivation film surface of Example 2 is as follows Figure 6 As shown, the surface of the passivation film is evenly covered with nano-scale particles.
[0121] The blank case was only cleaned without passivation treatment.
[0122] In the control example, ALODINE C 6100, a chromating agent produced by Henkel of Germany, was used as a film-forming agent for passivation treatment.
[0123] Surface resistance test: Use an ohmmeter to measure the resistance of the passivation film surface, and determine the conductivity of the film layer based on Ohm's law of a closed circuit. The smaller the resistance, the better the conductivity, and vice versa.
[0124] Salt spray test: A neutral salt spray test was used, with a 5% sodium chloride aqueous solution (pH 6.5-7.2) as the spray solution, the test temperature was 35°C, and the salt spray sedimentation rate was 1-3 mL / (80 cm 2 ·h), the sedimentation volume is 1~2mL / (80cm 2 h), spraying the salt mist vapor in this state on the surface of the substrate to accelerate the corrosion rate of the metal.
[0125] The test results are shown in Table 1:
[0126] Table 1
[0127]
[0128]
[0129] The above data results can be compared to show that the synthesis of conductive corrosion-resistant nanomaterials and the implementation of the scheme can significantly improve the corrosion resistance of the film while reducing the film resistance, that is, improving the conductivity. Its comprehensive performance is significantly better than the chromizing agent ALODINE C 6100 product of Henkel Company of Germany. However, the scope of conductive corrosion-resistant nanomaterials exceeds the defined range, and the corrosion resistance and conductivity of its film are affected to varying degrees. The present invention can meet the compatibility requirements of the chemical conversion film pretreatment technology in the current precision devices in terms of conductivity / corrosion resistance / environmental protection of the film after treatment.
[0130] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a film-forming agent having electrical conductivity and corrosion resistance, characterized in that: The following steps are involved: Dissolving the conductive and corrosion-resistant nanomaterial, acrylic acid homopolymer and neutralizing agent in water to obtain the conductive and corrosion-resistant film-forming agent; The conductive and corrosion-resistant nanomaterial is prepared by the following method: adding zirconium salt, acid copolymer, oxidant and monomer to water in sequence at -2 to 2°C to react, and obtaining the conductive and corrosion-resistant nanomaterial after the reaction is completed; The acid copolymer is selected from one or more of acrylic acid-acrylate-sulfonic acid-phosphonate copolymer, acrylic acid-acrylate-hydrolyzed maleic acid copolymer and acrylic acid-acrylate-tartaric acid copolymer, and the monomer is selected from one or more of benzotriazole, phenol, thiophene and aspartic acid.
2. The preparation method according to claim 1, characterized in that: The molecular weight of the acrylic acid homopolymer is 1000-5000 Da.
3. The preparation method according to claim 1, characterized in that: The neutralizing agent is selected from one or more of ammonia water, ammonium carbonate, ammonium bicarbonate, monoethanolamine and polyaspartic acid.
4. The preparation method according to claim 1, characterized in that: The zirconium salt is selected from one or more of zirconium nitrate, zirconium oxychloride, zirconium carbonate and zirconium fluoride.
5. The preparation method according to claim 1, characterized in that: The oxidant is selected from one or more of ammonium persulfate, sodium persulfate, hydrogen peroxide and potassium permanganate.
6. The preparation method according to claim 1, characterized in that: The molecular weight of the acid copolymer is 3000-5000Da.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the water, zirconium salt, acidic copolymer, oxidant and monomer is (85-96):(1-5):(1-5):(0.1-0.5):(1-5).
8. A conductive and corrosion-resistant nanomaterial, characterized in that: The conductive and corrosion-resistant nanomaterial is prepared by the following method: adding zirconium salt, acid copolymer, oxidant and monomer to water in sequence at -2 to 2°C to react, and obtaining the conductive and corrosion-resistant nanomaterial after the reaction is completed; The acid copolymer is selected from one or more of acrylic acid-acrylate-sulfonic acid-phosphonate copolymer, acrylic acid-acrylate-hydrolyzed maleic acid copolymer and acrylic acid-acrylate-tartaric acid copolymer, and the monomer is selected from one or more of benzotriazole, phenol, thiophene and aspartic acid.
9. A film-forming agent having electrical conductivity and corrosion resistance, characterized in that: The film-forming agent with conductivity and corrosion resistance is composed of the following components in percentage by mass: 1% to 5% of the conductive and corrosion-resistant nanomaterial according to claim 8, 1% to 10% of acrylic acid homopolymer, 1% to 5% of a neutralizer, and the rest is water.
10. Use of the film-forming agent having conductivity and corrosion resistance as claimed in claim 9 in coating of metal surfaces.
Citation Information
Patent Citations
Novel corrosion and scale inhibitor, and preparation method and application thereof
CN108623020A
Treating agent for forming chemical film layer on metal surface and preparation method thereof
CN116590698A
